On global smoothness preservation by Bernstein-type operators - TALPĂU DIMITRIU, Maria (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
We study global smoothness preservation of a function f by sequences of Bernstein-type operators with respect to a certain modulus of continuity of order two. Mathematics Subject Classification (2010): 41A36, 41A17.